The usefulness of the story of the alchemical vessel in the understanding and psychotherapy of borderline conditions: a case study - Milton, Christopher (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
The principal intention of this study was to explore the heuristic value of the story of the alchemical vessel in understanding borderline conditions and pursuing their psychotherapy. It establishes the pertinence of the case study as a method of exploring the content and process of psychotherapy. The essential nature of story-telling is examined and the hypothesis is made that psychotherapy, borderline conditions, the myth of the alchemical vessel and the case study all reflect instances of story-telling. Towards the end of examining their mutual reflection, and thus heuristic value, elements of Jungian theory, the phenomenology of borderline conditions and case material are examined. Through the examination of certain shared themes which emerge from the story of the alchemical vessel and the material of psychotherapy it is established that there is indeed a metaphoric resonance between the different stories. Furthermore this resonance is useful in that it provides a secure vantage point as well as guidance towards effecting transformation for the client. The validity of the metaphoric resonance is examined and areas of weakness highlighted. Some suggestions are made concerning further research.
Keywords: Psychotherapy; Borderline personality disorder